Dietary Restriction for Kidney Protection: Decline in Nephroprotective Mechanisms During Aging - Andrianova, Nadezda V.; Buyan, Marina I.; Bolikhova, Anastasia K.; Zorov, Dmitry B.; Plotnikov, Egor Y. (Frontiers in Physiology, 2021)
Dietary restriction (DR) is believed to be one of the most promising approaches to extend the lifespan of different animal species and to delay deleterious age-related physiological alterations and diseases. Among others, DR was shown to ameliorate acute kidney injury (AKI) and chronic kidney disease (CKD). However, to date, a comprehensive analysis of the mechanisms of the protective effect of DR specifically in kidney pathologies has not been carried out. The protective properties of DR are mediated by a range of signaling pathways associated with adaptation to reduced nutrient intake. The adaptation is accompanied by a number of metabolic changes such as autophagy activation, metabolic shifts towards lipid utilization and ketone bodies production, improvement of mitochondria functioning and decreased oxidative stress. However, some studies indicated that with age, the gain of DR-mediated positive remodeling gradually decreases. This may be an obstacle if we seek to translate the DR approach into a clinic for the treatment of kidney diseases as most patients with AKI and CKD are elderly. It is well-known that aging is accompanied by impairments in a huge variety of organs and systems, such as hormonal regulation, stress-sensing, autophagy and proteasomal activity, genes expression and epigenome profile, increased damage to macromolecules and organelles including mitochondria. All these age-associated changes might be the reasons for the reduced protective potential of the DR during aging. We summarized the available mechanisms of DR-mediated nephroprotection and described ways to improve the effectiveness of this approach for an aged kidney.